Les élections européennes de 2014 : une analyse comparative des résultats aux échelles nationale et régionale - Christian Vandermotten; Pablo Medina Lockhart (EchoGéo)
The paper presents a synthetic cartography, at the regional scale, of the results of the 2014 European poll, with comparisons to 2009. It opens on a classification of the political parties, leading to an elementary typology : parties developing a leftist critics of the ruling forms of the European policy ; parties agreeing with the ruling trends of the European agenda, either on a social-democratic or labour basis, or on a liberal, conservative or christian-democratic one ; eurosceptic or europhobic parties, on the basis of rightist and/or nationalistic attitudes. The paper examines also other variables, as abstention. Some regional conclusions appear, as for the political patterns in the main metropolitan areas, but the maps remain mainly a collection of national patterns. At the European scale, the explicit agreement to the ruling forms of the European construction gathers only a quarter of the potential voters, significantly less than in 2009. Moreover eurosceptic and europhobic Britain, the electoral disinterest for Europe is the strongest in the new Central-Eastern European member States.